Rekonstruksi Kurikulum PKn Bermuatan Pendidikan Antikorupsi - Lubis, Elfahmi; Mahdi, Imam; Iqbal, Moch (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research discusses the reconstruction of the curriculum at the State High School level in Bengkulu City which contains anti-corruption education which is realized in the learning of Pancasila Citizenship. The research method used in this research is descriptive qualitative. The results of the research can be seen that the implementation of curriculum reconstruction containing anti-corruption education is better than those that do not implement curriculum reconstruction containing anti-corruption education in Civics learning. The conclusion of this research is that by implementing curriculum reconstruction containing anti-corruption education, it can be used as a strategy that can foster student anti-corruption in every line of life. Keywords: Curriculum, Reconstruction, Anti-Corruption Education, Civics